The strategic renewal process – the challenge of creating and capturing value - Mielcarek, Paweł (Proces odnowy strategicznej – wyzwanie kreowania i przechwytywania wartości, 2018)
Organization development should ensure the simultaneous creation of value for its customers and the capture of value by the business. The first task is to create future revenue streams through innovations, The second focuses on increasing efficiency by matching the existing components of the business model. Optimizing these imperatives is the basis for strategic renewal and organizational success. The article presents the author’s concept of a strategic renewal process comprising four stages: triggering changes, forming concepts, changes implementation, verifying and formalizing changes. These stages were analyzed by way of implementing strategic renewal – regulatory issues and value development – exploration and exploitation.
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 28-34
Keywords: strategic renewal; renewal processes; creating value; capturing value; organizational change